2007
DOI: 10.1143/jjap.46.l833
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence from Silicon Quantum Dots in Si Quantum Dots/Amorphous SiC Superlattice

Abstract: We prepared size-controlled silicon quantum dots superlattices (Si-QDSLs) by thermal annealing of stoichiometric hydrogenated amorphous silicon carbide (a-SiC:H)/silicon-rich hydrogenated amorphous silicon carbide (a-Si 1þx C:H) multilayers. Transmission electron microscope (TEM) observation revealed that silicon quantum dots were formed in only a-Si 1þx C:H layers. The size of silicon quantum dots can be controlled by the thickness of the a-Si 1þx C:H layers. It was found that hydrogen plasma treatment (HPT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
51
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 15 publications
2
51
0
Order By: Relevance
“…Recently, several reports have been published on the fabrication and physical properties of Si QDs embedded in amorphous SiC matrix [3][4][5][6]. It was found that Si QDs can be formed by thermal annealing amorphous SiC films and the photoluminescence band was shifted by adjusting the Si QDs size due to quantum confinement effect (QCE) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several reports have been published on the fabrication and physical properties of Si QDs embedded in amorphous SiC matrix [3][4][5][6]. It was found that Si QDs can be formed by thermal annealing amorphous SiC films and the photoluminescence band was shifted by adjusting the Si QDs size due to quantum confinement effect (QCE) [7].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Song et al [3,5] have studied the effect of annealing on microstructural properties of nc-Si/SiC structures prepared by magnetron co-sputtering. The optical and electrical properties of nc-Si/SiC multilayers have also been investigated and the tunable photoluminescence was found by controlling the dot size [6,7]. In order to further improve the device performance, it is crucial to understand the electronic properties of Si nanocrystals embedded in amorphous SiC matrix together with the microstructures and optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Thin-film silicon-based solar cells are commonly fabricated using plasma-enhanced chemical vapor deposition, electron beam evaporation, hot filament-assisted deposition, magnetron sputtering, and some other approaches that are compatible with the present-day microelectronic manufacturing processes [3][4][5][6]. These approaches are rapidly gaining momentum with the continuously increasing use of nanostructured materials to enhance solar cell performance [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%